ANALISIS STABILITAS LERENG DI JALAN NASIONAL PROVINSI SULAWESI TENGGARA, DI DESA RAWUA, KECAMATAN SAMPARA, KABUPATEN KONAWE - Prastia, M. Yuda; Dewi, Anggi Purnama Sari; Mulyati, Ely (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2026)
In Southeast Sulawesi, the Konawe Regency–Kendari City–Sampara District corridor experienced severe flooding in 2019, resulting in road inundation and multiple landslides, including a major failure at Km 22. This study investigates the mechanisms and contributing factors of the landslide by modeling the effects of river water level fluctuations, groundwater level changes, and scouring on slope stability using Slope/W software. The analysis reveals that rising river water levels increase the slope’s safety factor, whereas sudden drawdown conditions significantly reduce it, potentially triggering slope failure.Keywords: Failure, slope stability, Safety factor